Pelatihan Budidaya Jamur Dan Pembuatan Media Tanam Jamur Tiram Di Sulawesi Selatan - Ichwan K, Muh.; Husain, Nursuci Putri (Patria Artha Journal of Community (PKM), 2021)
Oyster mushroom is one of the most commonly processed mushrooms as food ingredients and has high economic value. Many people in the South Sulawesi area are interested in cultivation of oyster mushrooms, but inexperience about cultivation and making oyster mushroom growing media (baglog) in the South Sulawesi area has made people unable to cultivation the oyster mushrooms independently. The purpose of engagement was to provide training in the cultivation and manufacture of oyster mushroom growing media to the community, so that people can cultivate and make mushroom growing media. This training begins with the provision of cultivation materials and the manufacture of growing media for oyster mushrooms, as well as business prospects for oyster mushrooms. Then, the practice of guidance on making oyster mushroom growing media, sterilization and mushroom inoculation was carried out. After that, simulation and evaluation were carried out, where participants were formed in groups and did independent practice of making mushroom growing media. This activity was carried out in one of the oyster mushroom cultivation sites in the City of Parepare, South Sulawesi, namely "Sahabat Jamur". This activity is also supported by the Corporate Social Responsibility (CSR) Program of PT PLN Persero – Sulselrabar Region. The training was conducted from 2 to 4 July 2021, and continued post-training monitoring via Whatsapp Group. The evaluation results from this training show that the cultivation and manufacture of oyster mushroom growing media can be done independently by the community, especially in the South Sulawesi area. The prospect of oyster mushroom cultivation and its processing has a very big opportunity in South Sulawesi.Keywords: Cultivation, Baglog, Oyster mushroom, South Sulawesi, Sahabat Jamur